ESTIMATION OF SEDIMENT ACCUMULATION RATE IN JAKARTA BAY USING NATURAL RADIONUCLIDE UNSUPPORTED 210Pb - Ali Arman Lubis; Barokah Aliyanta; Yulizon Menry (Universitas Gadjah Mada, 2007)
The investigation of sediment accumulation rate has been carried out in Jakarta Bay. The aim of this study is to estimate the accumulation rate of sediment using natural radionuclide 210Pb as a tracer, through the profile of unsupported 210Pb. Sediment cores of 40 cm and 30 cm length were collected using gravity core from 2 locations (TJ22 and TJ17A) in Jakarta Bay. Samples were sliced at 2 cm length, prepared and analyzed using PIPS detector Alpha Spectrometer. The result shows that in TJ22 consist of 3 layers; LS1 in the depth of (0-2) cm as a mixing layer, LS2 (2-16) and LS3 (16-26) cm and TJ17A has 3 layers; LS1 in the depth of (0-6) cm, LS2 (6-18) cm and LS3 (18-24) cm. Accumulation rate of sediment of LS2 and LS3 in TJ22 are 0.583 cm/y and 0.074 cm/y and in TJ17A are 0,852 cm/y and 0.115 cm/y, respectively. The accumulation rate of sediment since 30 years ago is higher than previous period.